THE EFFECT OF CONVENIENCE-USE, SALES PROMOTION, AND CONSUMER TRUST ON MILLENNIALS CONTINUOUS INTENTION IN USING GOPAY DURING COVID-19 IN JAKARTA - Bela Satyagraha (Jurnal Ilmiah Mahasiswa FEB, 2020)
This research aimed to know the effect of convenience-use, sales promotion, and consumer trust on millennials continuous intention in using GoPay during Covid-19 in Jakarta. The samples were 65 respondents aged between 24-40 who have ever used GoPay at least once and live in Jakarta. This is a quantitative research with a purposive sampling method, and data was collected through questionnaires. The analysis techniques used are Pearson Product Moment, Cronbach’s alpha, multiple regression analysis, and classical assumption test. The F-value of 44.281 with sig. of 0.000 indicates the model is appropriate to be used as a prediction with R²= 68.5%. Based on partial analysis: 1) convenience-use have no significant effect on millennials continuous intention according to t-value = 0.448 with sig. > 0.05 (0.655); 2) sales promotion has a significant effect on millennial continuous intention with t-value = 4.368 and sig. < 0.05 (0.000); 3) consumer trust has a significant effect on millennials continuous intention with t-value = 5.822 and sig. < 0.05 (0.000). Therefore, millennials continuous intention in using GoPay during Covid-19 in Jakarta is affected by sales promotion and consumer trust.Keywords: convenience-use, sales promotion, consumer trust, millennials continuous intention